The Impact of Professional Accounting Commitment on The Reduced Risk of Reliance on Financial Statements in The Jordanian Islamic Banks - Harb, Ayman Saleh Mustafa (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the role that professional commitment plays in influencing the reduction of the risks of reliance on financial statements. The researcher designed a questionnaire consisting of (24) items, which was distributed to the study population consisting of Islamic banks in Jordan. This study concluded that there is an effect of the professional accounting obligation on the reduction of the risk of reliance on the financial statements in Islamic banks, and there is also an effect of the accounting professional commitment on the reliability of information in Islamic banks. The researcher recommended the necessity of applying the principles of Islamic values ​​in accounting professional commitment.
Keywords: accounting professional commitment; risk reduction; financial statements